Penerapan Hukum Benford Dalam Mendeteksi Potensi Fraud Pada Data Klaim JKN Rawat Inap Di RS X - Efri Tri Ardianto; Azizah Nur Pratiwi; Alinea Dwi Elisanti (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2025)
Fraud in healthcare services is any form of deception carried out by various parties in healthcare services to gain personal benefits beyond the profits obtained from normal practices. At RS X, there is a team called the National Health Insurance (JKN) Fraud Prevention Team, which functions to ensure that the quality of healthcare services provided meets the applicable standards. One of the methods to analyze the distribution of abnormal data in a dataset is by using the concept of Benford's Law. The purpose of this research is to detect potential fraud in inpatient JKN claim data at RS X using Benford's Law. The type of research used is descriptive quantitative research. The population in this study is the JKN inpatient claim data for the period from August 2024 to October 2024, consisting of 11,789 rows of data. The use of Benford's Law to examine the differences in the "Hospital Rate" values shows that there is no difference in the pattern between the actual frequency and the expected frequency according to Benford's Law. The hypothesis test using chi-squared where the null hypothesis of the study is accepted, namely that the first digit numbers in the "Hospital Rates" column from August to October 2024 are distributed according to Benford's law.